To determine which of the given polynomials divides evenly by the divisor \(x + 3\), we will perform polynomial long division for each option. A polynomial divides evenly by \(x + 3\) if the remainder is 0 after the division.
A. \(3x^2 - 6x + 9\)
- Divide the leading term: \(3x^2 ÷ x = 3x\).
- Multiply \(3x\) by \(x + 3\): \(3x^2 + 9x\).
- Subtract: \[ (3x^2 - 6x + 9) - (3x^2 + 9x) = -15x + 9. \]
- Divide the leading term: \(-15x ÷ x = -15\).
- Multiply \(-15\) by \(x + 3\): \(-15x - 45\).
- Subtract: \[ (-15x + 9) - (-15x - 45) = 54. \]
Remainder: 54 (not divisible).
B. \(x^3 - 3x^2 - 13x + 15\)
- Divide the leading term: \(x^3 ÷ x = x^2\).
- Multiply \(x^2\) by \(x + 3\): \(x^3 + 3x^2\).
- Subtract: \[ (x^3 - 3x^2 - 13x + 15) - (x^3 + 3x^2) = -6x^2 - 13x + 15. \]
- Divide the leading term: \(-6x^2 ÷ x = -6x\).
- Multiply \(-6x\) by \(x + 3\): \(-6x^2 - 18x\).
- Subtract: \[ (-6x^2 - 13x + 15) - (-6x^2 - 18x) = 5x + 15. \]
- Divide the leading term: \(5x ÷ x = 5\).
- Multiply \(5\) by \(x + 3\): \(5x + 15\).
- Subtract: \[ (5x + 15) - (5x + 15) = 0. \]
Remainder: 0 (divisible).
C. \(x^3 - 5x^2 + 10x - 15\)
- Divide the leading term: \(x^3 ÷ x = x^2\).
- Multiply \(x^2\) by \(x + 3\): \(x^3 + 3x^2\).
- Subtract: \[ (x^3 - 5x^2 + 10x - 15) - (x^3 + 3x^2) = -8x^2 + 10x - 15. \]
- Divide the leading term: \(-8x^2 ÷ x = -8x\).
- Multiply \(-8x\) by \(x + 3\): \(-8x^2 - 24x\).
- Subtract: \[ (-8x^2 + 10x - 15) - (-8x^2 - 24x) = 34x - 15. \]
- Divide the leading term: \(34x ÷ x = 34\).
- Multiply \(34\) by \(x + 3\): \(34x + 102\).
- Subtract: \[ (34x - 15) - (34x + 102) = -117. \]
Remainder: -117 (not divisible).
D. \(5x^2 + 7x - 12\)
- Divide the leading term: \(5x^2 ÷ x = 5x\).
- Multiply \(5x\) by \(x + 3\): \(5x^2 + 15x\).
- Subtract: \[ (5x^2 + 7x - 12) - (5x^2 + 15x) = -8x - 12. \]
- Divide the leading term: \(-8x ÷ x = -8\).
- Multiply \(-8\) by \(x + 3\): \(-8x - 24\).
- Subtract: \[ (-8x - 12) - (-8x - 24) = 12. \]
Remainder: 12 (not divisible).
Conclusion:
The only polynomial from the options that divides evenly by \(x + 3\) is B: \(x^3 - 3x^2 - 13x + 15\).